Analisis Semiotika Makna Kasih Sayang Pada Lirik Lagu “Ayah” Karya Rinto Harahap - Estrada, Perindo; Indrawati , Indrawati; Marianti, Lena (CV. ITTC INDONESIA, 2023)
This research is about semiotic analysis of the meaning of affection in the lyrics of the song Ayah by Rinto Harahap. Music is a work of art that comes from several elements such as melody, harmony, composition, rhythm, tone and rhythm which produce a pitched sound and has its own characteristics. A piece of music usually depicts or conveys a message that is felt by the composer or addressed to the listener. Music has various types including pop, dangdut, jass, koplo, rock and so on. In music there are lyrics that represent the state or anxiety of the music creator so that it influences the listener's feelings or behavior which is a response to the message contained in the music. It was this message that made the researchers take the initiative to analyze the meaning of love contained in the lyrics of Rinto Harahap's father's song. The aim to be achieved from this research is to analyze the meaning of affection contained in the lyrics of the song Ayah by Rinto Harahap. This study uses a qualitative method with Rolland Barthes' theory known as the theory of analysis using signs: denotation, connotation, and myth. The results in this study indicate that there is a meaning of a child's affection for longing for a father whose whereabouts are unknown. Where this longing is poured or described in the lyrics of the father's song by Rinto Harahap. The son hopes that his father can listen to the song and know that he really misses the memories of the time together that he can no longer feel. He really hoped that he could be reunited with his father.